The invention of the classroom: republic, citizenship, and school space in Colombia: 1819–1830. - Cardenas-Herrera, John Jairo (Paedagogica Historica, 2021)
This article studies the invention of the classroom in a time of crisis – the one experienced after the independence war and in the framework of the Republic of Colombia building process (1819–1830). At that time, the expectations about the future were greater than the experiences about the past and there was confidence about the role of education in the process of transformation of the former vassal into Republican citizen. At that time, school practices were followed into the classroom that sought the distribution of the bodies in the classroom, the planning and synchronisation of the times in which the children were in school. The aim of all these school educational practices was the constitution of a republican citizen: disciplined, adherent to the norms, times, and instructions, and who recognised his place in a highly hierarchical society.